Pengembangan Media Pembelajaran Berbasis Multimedia Interaktif Pada Mata Pelajaran Administrasi Sistem Jaringan - Fachrul Faisal Ibrahim; Moh Hidayat Koniyo; Sitti Suhada (Inverted: Journal of Information Technology Education, 2021)
Abstract A preliminary study conducted in class XI TKJ at SMK Negeri 1 Limboto manages to identify a problem in network system administration subject particularly related to its conventional method of teaching. With this condition, students are no longer excited about the learning process, which eventually influencesthe teaching and learning process. The research aims to design an interactive multimedia-based learning media in network system administration subject in class XI TKJ of SMK Negeri 1 Limboto. This is a research and development which refers to Borg and Gall model prior to being tested to the user (student), the design learning media is validated by media expert and content expert. The data from both experts are collected by employing media eligibiliy test questionaire. The research finding show that (1) validation of media expert achieves a total score of 76 (89,41%) and (2) validation of content expert achieves a total score of 65(86,66%). After going through a set of validation, the learning media is tested on the user. The result of test reveals that the entire responses of students on the interactive multimedia-based learning media obtain a score of 1200 (90,91%) in conclusion, the learning media is eligible to use as an alternative in the teaching and the learning process, particularly in network system administration subject.Keywords: Interactive Multimedia, Eligibility, Network System Administration